Floodplain inundation in the Murray–Darling Basin under current and future climate conditions - Jin Teng; Francis H. S. Chiew; Hongxing Zheng; Ang Yang; David J. Penton; Catherine Ticehurst; Steve Marvanek; Jai Vaze; Fathaha Khanam; David A. Post; Carmel Pollino (Scientific Reports)
Abstract Predicting floodplain inundation under a changing climate is essential for adaptive management of water resources and ecosystems worldwide. This study presents a framework combining satellite observations and hydrological modeling to explore changes in floodplain inundation. We examine variability, trends, and frequency of inundation across the Murray–Darling Basin (MDB), Australia’s largest river system, over the past 35 years (1988–2022). Our analysis shows that annual maximum 30-day runoff is a primary hydrological factor influencing floodplain inundation. Using this metric as a proxy, we found that floodplain inundation, if driven solely by hydroclimate conditions, would have been more frequent in the recent decades (1988–2022) compared to the century-long baseline (1900–2022), especially in the southern basin. Despite projected declines in water availability under climate change in MDB, floodplain inundation appears to be less affected. The projected changes in floodplain inundation vary by region, influenced by local hydroclimate, human intervention, and the balance between projected more intense extreme rainfall and drier catchment conditions. This framework provides valuable insights into water resource planning and environmental management, with potential applications beyond the MDB.